HUBUNGAN SENAM MARYAM PADA MASA KEHAMILAN DENGAN EPISIOTOMI - Neng Kurniati; Linda Yulyani; Rahma Novita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Episiotomy is a medical procedure of cutting the perineum including the mucous membranes of the vagina, tissues, muscles and perineal fascia as well as the foreskin of the perineum. About 85% of women who give birth vaginal spontaneously experience perineal trauma by 32-33% due to episiotomy. Perineal rupture, whether caused by an episiotomy or spontaneous rupture, will cause bleeding, leave pain and increase the risk of post partum infection. Exercise during pregnancy is recommended to be started or continued for normal pregnant women so that their delivery is safe and smooth. This research is a true experiment with post test only design. The research sample was primigravida women who were >32 weeks pregnant who had been screened using the PAR-Q physical readiness questionnaire. It was carried out at the Independent Midwife Practice (PMB) of Sleman Regency, Yogyakarta in Kalasan, Ngemplak and Prambanan sub-districts. Tthe intervention group being given Maryam exercises and the controls being given basic pregnancy exercises. To determine the respondents in the intervention or control group, single-blinded randomization was carried out. Data analysis used the fisher's exact test. The results showed p = 0.045 (p <0.05) which showed that Maryam exercise in pregnancy was associated with reduced episiotomy and OR 0.1 indicated that the chance of reducing episiotomy was 0.1 times higher in Maryam exercise compared to basic pregnancy exercise.Keywords: Maryam Exercise, Pregnant Exercise, Episiotomy, perineal rupture